Effects of running skill and speed on limb coordination during submaximal and maximal sprinting - Whitacre, T. D.; Stearne, D. J.; Clark, K. P. (Journal of Biomechanics, 2024)
In locomotion, the relative phasing of the limbs changes with speed and provides valuable insight to neuromuscular control of gait. At present, it is unknown if individuals trained in sprinting coordinate their limbs differently than runners from other athletic backgrounds. Therefore, we aimed to characterize the effects of speed and skill on lower limb coordination. Twenty-five physically active (PA) and fifteen track and field (TF) athletes performed 40 m running trials at self-selected speeds, from jogging to maximal sprinting. We measured lower limb kinematics during steady-speed running, and quantified coordination using continuous relative phase (CRP) methods for interlimb pairs (Thigh-Thigh, Shank-Shank) and intralimb pairs (Shank-Thigh). Regression techniques showed between-group differences in scaling of coordination with speed during the stance phase, such that coordination was significantly more antiphase during jogging and running speeds in TF. During flight the scaling between groups was similar, but there were persistent and significant differences in coordination across all speeds. Comparing only the maximal speed trials, we found interlimb coordination was significantly more antiphase for TF in both stance and flight. In all cases, Shank-Shank coordination showed the largest between-group differences. Our results demonstrate the importance of interlimb coordination at maximal sprint speed, particularly during the flight phase and between shank segments. Between-group differences in coordination at slower speeds suggest a selective tuning of coordination in trained runners. We speculate differences in limb coordination are due to acquired motor patterns from optimizing forward velocity and its mechanical determinants, which differ particularly during flight/swing and between shank segments.